Stretch reflex sensitivity: effects of postural and muscle length changes - He, J (IEEE transactions on rehabilitation engineering, 1998)
In this study, a combination of clinical evaluation, laboratory testing, and model simulation of spasticity is performed under various postural conditions to investigate the changes in the sensitivity and specific mechanisms of spasticity. Fifty-nine multiple sclerosis patients participated in the study and received spasticity evaluation based on both the Ashworth scale and the pendulum test. Spasticity was found to increase in the pendulum test when the subjects were tested in a supine posture, compared to when they were sitting. Three patterns of stretch reflex response were seen for similar leg swing trajectories. While it was clear that the increased stretch of rectus femoris in the supine posture contributed to the increased spasticity, the results of modeling showed that other more complex factors were also involved. The supraspinal descending modulation associated with postural control may play a more dominant role in the severity of spasticity. The results suggest that the biomechanical test of spasticity should be performed for several different postures or ranges of movement with muscle activities monitored simultaneously, so that the effect of various factors can be examined. The work also indicates that a neuromusculoskeletal model with detailed muscle dynamics and stretch reflex loops is a valuable tool for investigating the neural mechanisms of spasticity.